Durability performance of concrete with recycled aggregates from construction and demolition waste plants. (15th February 2015) - Bravo, Miguel; de Brito, Jorge; Pontes, Jorge; Evangelista, Luís
Highlights: Concrete with fine and coarse recycled aggregates (RA) from construction and demolition waste (CDW). CDW from five recycling plants with a wide variety of compositions. Analysis of the influence of the RA's source, composition, size and incorporation ratio. Analysis of the feasibility of the use of these RA in terms of concrete's durability performance. Abstract: This research intends to analyse the durability performance of concrete with recycled aggregates (RA) from construction and demolition waste (CDW) from various locations in Portugal. To that effect water absorption by immersion and capillarity, carbonation resistance and chloride ion penetration resistance tests were performed. To better understand the experimental results, the characteristics of the various aggregates (natural and recycled) used in the production of concrete were analysed in detail. The composition of the RA was determined and various physical tests of the aggregates were performed. 33 concrete mixes with RA from different CDW recycling plants were evaluated in order to understand the influence that the RA's collection point, and therefore their composition, has on the characteristics of the concrete mixes produced. Both coarse and fine RA were used to determine the influence of their size on concrete's performance. The analysis of the durability performance allowed concluding that the use of RA is highly detrimental. This is mostly true when fine RA are used. The carbonation resistance is the property most affected by the use of RA, leading to increases in the carbonation depth between 22.2% and 182.4% for the various RA types. However, the most influencing factor is by far the RA's composition.